A Ten-Year Study on Risk Factors of Orchiectomy in Testicular Torsion - Rulianov Rulianov; Kuncoro Adi; Ferry Safriadi (Faculty of Medicine, Universitas Padjadjaran, 2022)
Testicular torsion is a common urological emergency among children, peaking in neonates and pubertal age with an incidence rate of 3.8 in 100.000 (0.004%) annually. This study aimed to explore the characteristics of testicular torsion cases and risk factors for orchiectomy in testicular torsion patients. This was a retrospective study on medical records of patients diagnosed with testicular torsion underwent surgery at the urology department of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from January 2009 to August 2019. Patient characteristics including age, duration of symptom, location, etiology, and degree of torsion were analyzed. A total of 86 cases of testicular torsion were identified, with most cases (54 cases, 62.8%) occured at the mean age 14.67 ± 2.4 years old. Most patients (69 patients, 80.2 %) arrived more than six hours after the onset, and 65 (75.5%) and 4 (4.6%) of them underwent orchiectomy and orchidopexy, respectively. The remaining patients (17 patients, 19.8%) came less than 6 hours after the onset and only 8 (9.3%) and 9 (10.4%) underwent orchiectomy and orchidopexy, respectively. Both duration of torsion (p = 0.000, P<0.05) and degree of torsion (p = 0.006 , P<0.05) were significantly correlated with orchiectomy. In conclusion, the risk factor for orchiectomy is strongly related to duration and degree of torsion. The chance for testis salvation increases if torsion happens before 4.5 hours and the degree of torsion is below 180 degrees. Prompt diagnosis and treatment is the only key to testicular salvation.